Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude

Guião metodológico para gestão de terras urbanas: gestão de terras urbanas municipais - República de Moçambique: Ministério do Meio Ambiente (República de Moçambique: Minitério da Terra e Ambiente, 2020)
O objectivo deste manual é auxiliar os municípios no contexto da gestão de terra, com especial foco na regularização do DUAT (Direito de Uso e Aproveitamento da Terra) e respectivas construções. O manual pretende abranger o maior número de situações que ocorrem no dia-a-dia, apresentando soluções apoiadas na presente legislação. Pretende-se que o manual seja um valioso material de apoio à capacitação das equipas técnicas dos municípios e áreas urbanas. O objectivo do manual é igualmente informar o público e capacitar os técnicos dos municípios e outras instituições com melhores técnicas e práticas para aperfeiçoar a gestão de terras de acordo com a legislação actual.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; governance / governação; land governance / gestão de terra; urbanization / urbanização

Mozambique Urbanization Review: Accelerating Urbanization to Support Structural Transformation in Mozambique (World Bank Group, 2017)
The Mozambique Urbanization Review aimed at contributing to the country’s policy and institutional reform agenda on how to harness the full potential of urbanization to promote economic growth and poverty reduction. The study carried out in-depth analyses of the urbanization process, uncovering how urbanization has been influenced by national, regional, and international factors. It identified and analyzed key policy and institutional constraints in increasing the economic benefits of urbanization, including economic, transport, land, and decentralization policies. The study concluded that faster urbanization could increase the pace of economic growth and poverty reduction, but this should not be achieved at the expenses of investments in rural development and agriculture. However, constraints in the creation of productive urban jobs, limited connectivity throughout the system of cities, and dysfunction urban land markets have undermined its economic outcomes. Based on the main findings, the study proposed an emerging national urban reform agenda to enhance the benefits from urbanization in Mozambique focused on: (i) strengthening rural-urban linkages, including reforms to local government finances, enhancing trade and commuting flows; (ii) making urban land systems more equitable and efficient; and, (iii) deepening decentralization to provide a broader remit to municipalities for urban planning and domestic resource mobilization.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; urbanization / urbanização

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

Nationalism, urban poverty and identity in Maputo, Mozambique - Sumich, Jason (2010)
This paper examines the changing perceptions of Frelimo's nationalist project amongst members of the middle class in Maputo, Mozambique's capital. I argue that nationalism in Mozambique created a system of meaning and new forms of identity that are especially relevant for more privileged urbanites. However, growing urban poverty and inequality has had an effect throughout the social spectrum in Mozambique. The self-same set of nationalist values provides a critique for the failings of the regime as everyday life continually conflicts with the government's message of unity and progress for all and this is causing a loss of support even among the regime's beneficiaries.
ISSN: 1749-1797 Issue: 68 Num Pages: 15 Number: 68 Place: London, UK Publisher: Crisis States Research Centre, London School of Economics and Political Science
Keywords: G - Mozambique / Moçambique; L - english / inglês; urbanization / urbanização

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Monitoring and Evaluating Mozambique’s Poverty Reduction Strategy PARPA 2006-2008. A Synopsis of Three Qualitative Studies on Rural and Urban Poverty. - Tvedten, Inge; Rosário, Carmeliza; Paulo, Margarida (Chr. Michelsen Institute, 2009)
The purpose of this synopsis is to facilitate discussions between the government, civil society organisations, donors and other stakeholders in Mozambique’s efforts to reduce poverty and, more specifically, to contribute to the Impact Assessment Report (Relatótio de Avaliação de Impacto, RAI) which is to be carried out in 2009. We will focus on our main findings and preliminary conclusions, and will to the extent possible avoid repeating data found in the original reports to ease accessibility. The discussions related the synopsis will also be used to further identify the most relevant topics and approaches for the final three studies, in order to secure their maximum utility for the government’s monitoring and evaluation programme. The synopsis will be divided into six parts following this Introduction. In Chapter 2 we briefly account for the analytical framework and methodological approaches of the studies. In Chapter 3 we present what we have identified as aspects of Mozambique’s political economy with particular impacts on the situation in local communities. In Chapter 4 we analyse the main features of the political context at the level of districts through which poverty reduction is implemented. In Chapter 5 we present the main findings from the adapted surveys we have carried out, with a focus on the similarities and differences between the three areas of study. In Chapter 6 we assess the outcome of our qualitative and participatory approaches to our analyses. And finally, in Chapter 7, we present preliminary conclusions and recommendations from the first three studies and outline the approach of the three follow-up studies.
E-version: ISBN 978-82-8062-340-9
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

"Xiculungo" - Social relations of urban poverty in Maputo, Mozambique - Paulo, Margarida; Rosário, Carmeliza; Tvedten, Inge; Chr. Michelsen Institute (Chr. Michelsen Institute (CMI), 2007)
This is the second in a series of six participatory and qualitative studies of poverty in Mozambique, done with the objective of supporting the government in monitoring and evaluating the ongoing Action Plan for the Reduction of Absolute Poverty, PARPA II (GdM 2005). The first report looked into social relations of rural poverty in northern Mozambique, with special reference to the District of Murrupula in the Nampula province (Tvedten, Paulo and Rosário 2006). This report will analyse social relations of urban poverty, with special reference to four settlement areas (bairros) in Mozambique’s capital Maputo (see Terms of Reference, Annex 1). The Government of Mozambique and donors have invested considerable effort and resources in economic development and the reduction of poverty. While this has led to improvements in terms of an economic growth of 8 percent per annum over the past ten years (Arndt et al. 2006) and a reduction in the proportion of Mozambicans living in poverty from 69 to 54 percent (INE 2004), key socio-economic indicators are still very serious: GDP per capita is USD 1,117, the adult literacy rate is 46.5 percent, and life expectancy at birth is 41.9 years (World Bank 2006; UNICEF 2007). This places Mozambique at number 172 of 177 countries in UNDP’s Human Development Index, which makes it the least developed country in Southern Africa (UNDP 2007). Research-based information about poverty is recognised as important for Mozambique’s poverty reduction strategies, as these are expressed in the Government’s Five Year Plan (GoM 2005) and the related PARPA II (GdM 2005). Key data for the monitoring and evaluation of poverty in Mozambique stem from the National Census (INE 1997 and forthcoming 2008), the National Household Survey IAF (INE 1997 and 2004) and the National Demographic and Health Survey (MdS 2005), as well as a number of analyses by the Government of Mozambique based on these data (see e.g. DNPO 2004; Chiconela 2004; Maximiano et al. 2005). In addition, international organisations have commissioned several studies on their own, of which those undertaken by UNDP (2006), UNICEF (2007) and the World Bank (2007) are the most recent and comprehensive
OCLC: 874829175
Keywords: G - Mozambique / Moçambique; Important; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
ISSN 0805-505X ISBN 82-8062-172-5
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização